2009
DOI: 10.1016/j.jpainsymman.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Indwelling Catheters for the Management of Refractory Malignant Ascites: A Systematic Literature Overview and Retrospective Chart Review

Abstract: The safety and efficacy of indwelling intraperitoneal (IP) catheters for the management of refractory malignant ascites is unclear. A systematic literature overview and retrospective chart review of patients with malignant refractory ascites who underwent indwelling IP catheter placement was performed. Standardized literature abstraction and chart review templates were used to ensure that consistent information was collected. Fifteen publications met literature search criteria, representing 221 patients. Tenck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 21 publications
0
60
0
2
Order By: Relevance
“…Therefore, to minimize repeated paracenteses and frequent hospital visits, permanent drains are frequently used. 21,23,34 We observed in our cohort that 36% (n = 64) of patients underwent paracenteses only as the means of managing ascites, with 58% of this subgroup (n = 37) having 1 to 2 paracenteses, and only 14% (n = 9) having ≥ 3 paracenteses. Nearly two-thirds of the cohort required a permanent catheter (n = 116; 64% of total analyzed cohort) to obtain palliation, and we observed that 42% (n = 49) patients required ≥ 3 paracenteses to address ascites before a catheter was placed ( P < .001).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, to minimize repeated paracenteses and frequent hospital visits, permanent drains are frequently used. 21,23,34 We observed in our cohort that 36% (n = 64) of patients underwent paracenteses only as the means of managing ascites, with 58% of this subgroup (n = 37) having 1 to 2 paracenteses, and only 14% (n = 9) having ≥ 3 paracenteses. Nearly two-thirds of the cohort required a permanent catheter (n = 116; 64% of total analyzed cohort) to obtain palliation, and we observed that 42% (n = 49) patients required ≥ 3 paracenteses to address ascites before a catheter was placed ( P < .001).…”
Section: Discussionmentioning
confidence: 67%
“…20 Conversely, a major risk pertaining to an indwelling catheter is the development of peritonitis, and the literature shows that the risk is higher in untunneled compared with tunneled catheter types. 21 Another type of permanent drain is a peritoneal venous shunt, 22 including the LeVeen shunt, the first prototype of its kind. 23 Nevertheless, due to its poor efficacy and risk of serious complications, including port occlusion, disseminated intravascular coagulation, and short life, it was later replaced by the Denver shunt.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Very few cases of peritonitis associated with peritoneal ports have been described 4,8 ; uncomplicated cellulitis has been suggested as the most common infectious complication, occurring in 18% in one series. 9 Hypotension, consistent with other series, was not significant in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The relative inefficiency of diuretics in specific types of MA is likely because of different pathophysiologic mechanisms for fluid accumulation 14. A response to diuretics has been observed in patients with ascites secondary to massive hepatic metastases who have a serum:ascitic albumin gradient of >11 g/L 12,15…”
Section: Introductionmentioning
confidence: 99%